Pengembangan Activity Book Berbasis STEAM pada Pembelajaran IPAS Materi Bagaimana Kita Hidup dan Bertumbuh Kelas V SDN 1 Demuk Pucanglaban Tulungagung - Yusnia Septiani; Nourma Oktaviarini (Departement of Mathematics Education, 2024)
This research is motivated by the learning process in the classroom which still listens to the teacher's explanation and pictures as teaching and learning tools. This makes students easily feel bored so that students' interest in learning decreases. This study aims to develop, test the validity and applicability of STEAM-based activity book media development products in IPAS learning material on how we live and grow in grade V SDN 1 Demuk Pucanglaban Tulungagung. This research is a method using the ADDIE model which consists of the analysis (Analyze), design (Design), development (Development), implementation (Implementation), and evaluation (Evaluation) stages. Data collection techniques were carried out using media validity tests, materials, and questionnaires. The instruments that researchers use are media expert validation sheets, material expert validation sheets, and student questionnaire sheets. The results obtained in this study are media validation by media validators obtained a percentage of 90% with a very valid category, while the assessment of the material validator obtained a percentage of 92.5% with a very valid category, and the assessment of student responses obtained a percentage of 92% with a very valid category. Those it can be concluded that the research results of